2009
DOI: 10.1111/j.1600-0501.2008.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination with α‐tricalcium phosphate and simvastatin on bone regeneration

Abstract: When combined with alpha-TCP particles, 0.1 mg simvastatin is the optimal dose for stimulation of the maximum bone regeneration in rat calvarial defects without inducing inflammation and it could be applied as an effective bone graft material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
5
12

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 43 publications
5
83
5
12
Order By: Relevance
“…5,9,10 Others, however, have found no beneficial effects. 9,19,20 The ideal doses and carriers have yet to be determined, and the issue remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,9,10 Others, however, have found no beneficial effects. 9,19,20 The ideal doses and carriers have yet to be determined, and the issue remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The speed at which the carrier releases the drug also plays a role in the local concentration and effectiveness of simvastatin. Stein et al 7 used 0.1 mg of simvastatin in methylcellulose gel and reported no stimulation of bone formation, whereas Nyan et al 10 used the same amount of simvastatin in combination with alpha-tricalcium phosphate and reported significant new bone formation, greater than that obtained using 0.25 and 0.5 mg of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Promotes early consolidation of the graft [24][25][26][27] • Hastens the mineralization of the graft [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Nyan et al concluded that simvastatin combined with calcium sulfate caused substantial bone regeneration in rat calvarial defects; however, with a considerable soft tissue inflammation and scabbing of the skin overlying the calvaria. Thus, the local effects of simvastatin could be doseand carrier-dependent [26].…”
Section: Discussionmentioning
confidence: 99%